Progress in imaging methods: insights gained into Plasmodium biology - Niz, Mariana De; Frischknecht, Friedrich (Nature reviews. Microbiology, 2017)
Over the past decade, major advances in imaging techniques have enhanced our understanding of Plasmodium spp. parasites and their interplay with mammalian hosts and mosquito vectors. Cryoelectron tomography, cryo-X-ray tomography and super-resolution microscopy have shifted paradigms of sporozoite and gametocyte structure, the process of erythrocyte invasion by merozoites, and the architecture of Maurer's clefts. Intravital time-lapse imaging has been revolutionary for our understanding of pre-erythrocytic stages of rodent Plasmodium parasites. Furthermore, high-speed imaging has revealed the link between sporozoite structure and motility, and improvements in time-lapse microscopy have enabled imaging of the entire Plasmodium falciparum erythrocytic cycle and the complete Plasmodium berghei pre-erythrocytic stages for the first time. In this Review, we discuss the contribution of key imaging tools to these and other discoveries in the malaria field over the past 10 years.
Published online: 28 Nov 2016
Gesehen am 04.09.2018